Islamization of Mandailing Natal After the Padri War - Amliansyah Amliansyah; Siti Fatimah (Science and Environmental Journal for Postgraduate, 2022)
This study is about the Islamization of Mandailing Natal after the Padri war. This research portrays the history and the development of Islam in Mandailing Natal to analyze the uniqueness of the Islamization process. This was done by looking at the carriers of Islam in the region, the religion itself, and the media used in the process which was used to analyze how the development of Islam was in Mandailing Natal. As for the informants, historians and cultural practitioners of Mandailing Natal were the informants of this research. The method used was qualitative with a historical study. The techniques used to collect the data were observations, interviews, and documentation. The results of the study showed that Islamization in Natal of Mandailing District began before the reform movement in Minangkabau. The Islamization process took place in the 18th century CE and the carriers were Islamic clerics from Minangkabau, namelySyekh Abdul Fattah (1975-1985 CE), Syekh Abdul Rauf (1896 CE), Syekh Abdul Malik (1905 CE), also known as Baleo Natal, who was a student of Syekh Abdul Fattah. As the Paderi Movement (1816-1837 CE) entered Mandailing Region, Islamization took place massively which was done by the figures of the Paderi Movement. In terms of the Islamization pattern in Mandailing natal, the patterns were assimilation and accommodation pattern. The Islamization process in Mandailing Natal was done in four stages. The first stage (Conversion) was the stage of introducing Islam to those who had not followed the Islamic teaching. The second stage (Intensification) was the stage of teaching Islam and strengthening the existence of Muslims. The third stage (Actualization) was the stage of deepening Islam and applying the concept of Islam in social life as well as confronting kafir authorities. The fourth stage was the reformation stage which was marked by reforming thoughts and Islamic life in the society. Islam has kept on growing positively in terms of quality and quantity in Mandailing Natal.